The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18632/oncotarget.18780
|View full text |Cite
|
Sign up to set email alerts
|

Stress inhibits tryptophan hydroxylase expression in a rat model of depression

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) dysfunction is associated with the pathophysiology of depression. Tryptophan hydroxylase (TPH), the rate-limiting enzyme in 5-HT biosynthesis, is believed to have essential role in many mental disorders, including depression. In the present study, we generated a rat model of depression by exposing the animals to stress, and the rats were then treated with paroxetine. The results indicated that the concentration of 5-HT in the brain and liver tissues were significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
4
29
0
6
Order By: Relevance
“…Therefore, since tryptophan hydroxylase is the enzyme responsible for the synthesis of serotonin, a TPH immunohistochemistry was carried out in the hypothalamic area to clarify the SQE mechanism that induced an elevation in the serotonin levels. The rats in control group exhibited a lower TPH-IR cells number in the hypothalamic nuclei as in this study [64], while the SQE 100 and 300 administration enhanced these cells significantly in the anterior hypothalamic nucleus (AN), ventromedial hypothalamic nucleus (VMH), paraventricular hypothalamic nucleus (PVN), and arcuate nucleus (Arc).…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, since tryptophan hydroxylase is the enzyme responsible for the synthesis of serotonin, a TPH immunohistochemistry was carried out in the hypothalamic area to clarify the SQE mechanism that induced an elevation in the serotonin levels. The rats in control group exhibited a lower TPH-IR cells number in the hypothalamic nuclei as in this study [64], while the SQE 100 and 300 administration enhanced these cells significantly in the anterior hypothalamic nucleus (AN), ventromedial hypothalamic nucleus (VMH), paraventricular hypothalamic nucleus (PVN), and arcuate nucleus (Arc).…”
Section: Discussionsupporting
confidence: 57%
“…There are several conflicting studies on the expression pattern of TPH following exposure to stress. Still, it has been reported that the levels of 5-HT and TPH in the raphe nuclei of the brain stem are tightly linked to the development of a depressive disorder or depressive-like behaviors [ 28 30 ]. In the present study, although not statistically significant, all mice exposed to repeated RST showed a trend towards increased TPH expression selectively in the dorsal raphe nucleus, the largest serotonergic nucleus, depending on the duration of RST exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The next main finding of our study was that chronic venlafaxine administration in stressed rats decreased Tph1 protein expression in the basal ganglia and decreased the methylation status of the Tph1 promoter region in PBMCs; however, no changes were observed in the brain. On the other hand, Chen et al ( 2017 ) observed that stressed rats showed increased levels of Tph1/Tph2 promoter methylation, which was normalized by paroxetine (an SSRI), in the brain, liver and kidney. These differences may be related to the fact that the stressors used in the above study were much more severe and that the animal breeds that were used differed between studies.…”
Section: Discussionmentioning
confidence: 99%